Du Pont System Analysis in Financial Performance Assessment Registered Food and Beverage Company on the Indonesia Stock Exchange 2013-2022 - Sri Wahyuaningsih; Suharsono; Datu Beru (Indonesian Development of Economics and Administration Journal, 2022)
This study aims to determine the financial performance of food and beverage companies listed on the Indonesia Stock Exchange in 2013-2022 using the du pont system approach. The data used in this study is in the form of financial report data from 2013-2022. The analytical method in this research is a descriptive analysis method. From the data analysis conducted on the financial statements of the last ten years using the du pont system method at PT Indofood CBP Sukses Prosperous Tbk , PT Charoen Pokphand Indonesia Tbk and PT Indofood Sukses Prosperous Tbk during 2013-2022 it shows unstable financial performance. This can be seen from the unstable return on equity over the last ten years. This unstable return on equity was caused by several factors, including the increase in total costs which were not proportional to the increase in net profit after tax, so that net profit margins fluctuated. Inefficiency also occurs in sales that increase but are not proportional to net profit after tax. Nonetheless, total assets have increased despite fluctuations in total assets.